The Role of Bioethics in the System of Natural Sciences and Social Sciences - Hoshimov Sanjar Sultonbekovich (Central Asian Journal of Literature, Philosophy and Culture, 2022)
The article considers the interpretation of bioethics as a «bridge» between the natural and humanitarian sciences. Sources of bioethics are such disciplines as medicine, theology, philosophy and law. Modern bioethics is a «normal» science in the Kuhn sense of the word. Under «normal» science, T.Kuhn understood the discipline in which there is stubborn resistance to any kind of change. In the field of bioethics, the central place is occupied by the concept of principle. According to this concept, the basis for bioethical analysis should be the guiding ethical principles and rules.